AB0675 Is The Periodontal Clinical and Microbiological Condition in Spondyloarthritis Similar than Rheumatoid Arthritis?. (15th July 2016) - Giraldo Q, S.; Romero-sanchez, C.; Bautista-Molano, W.; Bello-Gualtero, J.M.; De-Avila, J.; Chila M, L.; Castillo, D.M.; Lafaurie, G.I.; Londoño, J.; Valle-Oñate, R.
Abstract : Background: The periodontal disease (PD) generates systemic impact given the increase in acute phase reactants related to the inflammatory. The relationship between Rheumatoid arthritis (RA) and PD is supported by pathological and immunological data but is not clear this association in Spondyloarthitis (SpA). The association between their respective disease activities and severities are less documented. Periodontal inflammation may affect disease activity and severity on patients with SpA. Objectives: To evaluate the association between clinical indices of PD and markers of disease activity in SpA patients and compare these markers in patients with RA and controls. Methods: The rheumatologic condition and periodontal status of 79 individuals with SpA, 59 patients with RA and 79 matched-controls were evaluated. Porphyromona gingivalis (Pg), IgG1, and IgG2 to Pg were determined. The C-reactive protein-, erythrocyte sedimentation rate-, HLA B 27, rheumatoid factor-RF, anti-citrullinated protein antibodies, and disease activity measures for SpA and RA were assessed. The rheumatologic Scores and periodontal condition were evaluated by two experienced and calibrated periodontists and rheumatologist. The groups were compared with Kruskal Wallis, Mann-Whitney U and Wilcoxon test's test and a paired t-test. The chi-square test was used to evaluate periodontal variables and SpA disease activity. The institutional Ethics Committee approved the study. Results: 79 SpA patients with the following subtypes were included: Ankylosing Spondylitis (AS) (19), undifferentiated SpA (46), and reactive arthritis (ReA) (14). SpA patients had a considerable frequency of periodontitis (55.7%). Of them, 39.2% were classified as moderate and 2.5% as severe periodontal condition. No differences was found in frequency of periodontal condition between subtypes. SpA patients showed lower levels of insertion loss compared to RA patients and the control group (p<0.05). A significant association was observed in microbiological variables of SpA patients. The frequency of ( P gingivalis) in the control group was 51.9% compared to 30% in SpA (p=0.015), especially in those with good response to NSAIDS (p= <0.05). Significant associations between the severity of periodontal involvement in RA patients was observed. 63.8% of RA patients had moderate severity disease (49.2%) and severe periodontitis (13.6%) (p=0.035) but not in SpA group. There were not association between disease activity measures in SpA, periodontal and severity condition. Conclusions: As compared to RA and healthy controls, periodontal condition in SpA patients was similar. Lower grades of severity and bacterial load were found. This suggests that an interdisciplinary treatment between periodontists and rheumatologists may help to modulate periodontal condition and prevent systemic impact References: Pischon N, Pischon T, Gülmez E, Kröger J, Purucker P, Kleber BM. Periodontal Diseases in Patients with ankylosing spondylitis. Ann Rheum Dis 2010;69:34–38. Białowąs K1, Swierkot J1, Radwan-Oczko M.Role of Porphyromonas gingivalis in rheumatoid arthritis and inflammatory spondyloarthropathies. Postepy Hig Med Dosw. 2014;68:1171–9. Disclosure of Interest: None declared